PID Controller Response to Set-Point Change in DC-DC Converter Control - Oladimeji Ibrahim; Nor Zaihar B Yahaya; Nordin Saad (Institute of Advanced Engineering and Science, 2016)
Power converter operations and efficiency is affected by variation in supply voltage, loads current, circuit elements, ageing and temperature. To meet the objective of tight voltage regulation, power converters circuit module and the control unit must be robust to reject disturbances arising from supply, load variation and changes in circuit elements. PID controller has been the most widely used in power converter control. This paper presents studies of robustness of PID controller tuning methods to step changes in the set point and disturbance rejection in power converter control. A DC-DC boost converter was modelled using averaged state-space mothod and PID controllers were designed with five different tuning methods. The study reveals the transient response and disturbance rejection capability of each tuning methods for their suitability in power supply design applications.